2019
DOI: 10.1177/1099800418824716
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients With Fibromyalgia in a Prothrombotic State?

Abstract: Objectives: The aim of this study was to investigate thrombosis-related parameters (blood coagulation parameters, platelet indices, red blood cell [RBC] count, and inflammatory markers) in patients with fibromyalgia (FM). Method: We carried out a case–control study with 35 women with FM and 12 age-matched healthy volunteers to analyze fibrinogen levels, prothrombin time, cephaline time, platelet count, platelet distribution width (PDW), mean platelet volume (MPV), RBC count, neutrophil-to-lymphocyte ratio, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
5
15
0
Order By: Relevance
“…In this regard, it has been reported that MPV is not as specific a marker of platelet activity as PDW because it increases during simple platelet swelling [22]. Moreover, other authors reported finding an inverse relationship between MPV and platelet count [23], as we observed in our previous study [7]. The increase in MPV values due to ROO consumption in the present study would not be negative, since it approximates values of patients with FM to those of healthy subjects [7].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In this regard, it has been reported that MPV is not as specific a marker of platelet activity as PDW because it increases during simple platelet swelling [22]. Moreover, other authors reported finding an inverse relationship between MPV and platelet count [23], as we observed in our previous study [7]. The increase in MPV values due to ROO consumption in the present study would not be negative, since it approximates values of patients with FM to those of healthy subjects [7].…”
Section: Discussionsupporting
confidence: 62%
“…In a previous study, we found altered levels of thrombosis-related parameters, including higher fibrinogen levels, PDW values and RBC counts, and lower MPV values in patients with FM in comparison to controls [7]. Results of the present study show that olive oil may return altered levels compared to those of the healthy controls (data from healthy subjects can be consulted at Molina et al, 2019 [7]). Curiously, although increased MPV values may be considered as a cardiovascular risk factor, our previous data showed significantly lower MPV values in FM patients that may be in a prothrombotic state when compared to healthy subjects [7].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations